Development of the 25-item Cardiff Visual Ability Questionnaire for Children (CVAQC). Issue 6 (27th May 2010) - Khadka, Jyoti; Ryan, Barbara; Margrain, Tom H; Court, Helen; Woodhouse, J Margaret
Abstract : Aims: To develop and validate a short questionnaire to assess self-reported visual ability in children and young people with a visual impairment. Methods: A list of 121 items was generated from 13 focus groups with children and young people with and without a visual impairment. A long 89-item questionnaire was piloted with 45 visually impaired children and young people using face-to-face interviews. Rasch analysis was used to analyse the response category function and to facilitate item removal ensuring a valid unidimensional scale. The validity and reliability of the short questionnaire were assessed on a group of 109 visually impaired children (58.7% boys; median age 13 years) using Rasch analysis and intraclass correlation coefficient (ICC). Results: The final 25-item questionnaire has good validity and reliability as demonstrated by a person separation index of 2.28 and reliability coefficient of 0.84. The items are well targeted to the subjects with a mean difference of −0.40 logit between item and person means, and an ICC of 0.89 demonstrates good temporal stability. Conclusion: The Cardiff Visual Ability Questionnaire for Children (CVAQC) is a short, psychometrically robust and a self-reported instrument that works to form a unidimensional scale for the assessment of the visual ability in children and young people with a visual impairment.